Protective effect of heat shock protein 70 against oxidative stresses in human corneal fibroblasts - Kim, YS; Han, JA; Cheong, TB; Ryu, JC; Kim, JC (KOREAN ACAD MEDICAL SCIENCES, 2004)
We evaluated DNA protection effect of heat shock protein (HSP) against cytotoxic effects of exogenous nitric oxide (NO) and reactive oxygen intermediate (ROI). Cultured human corneal fibroblasts were divided into 4 groups. Control (Group 1) was not exposed to a sub-lethal heat treatment. Other 3 groups were exposed to 43degreesC for 1 hr, then incubated at 37degreesC during different duration (1, 6, 24 hr, Group II, III, IV, respectively). Expression pattern of HSP 70 was analyzed by Western blot. Cell viability was measured by MTT assay and the relationship between HSP 70 expression and DNA damage was examined by terminal deoxyribonucleotidyl transferase mediated dUTP-digoxigenin nick and labeling (TUNEL) stain and single cell gel electrophoresis. Expression pattern of HSP 70 was dependent on recovery times. Cell viability following heat treatment was significantly increased and the TUNEL positive cell number was decreased at 6 hr. In single cell gel electrophoresis, tail moments were increased in a dose-dependent manner by SNAP and X/XO. Following heat treatment, tail moments showed decreased significantly at 6 hr. These results suggest that induction of HSP 70 by sub-lethal heat treatment is closely related with cytoprotective effects against oxidative stresses in human corneal fibroblasts.
Keywords: SHOCK-PROTEIN EXPRESSION; NITRIC-OXIDE; DNA-DAMAGE; IN-VITRO; CELLS; ELECTROPHORESIS; CYTOTOXICITY; RESISTANCE; APOPTOSIS